Um Eqüídeo Fóssil do Pleistoceno de Alegrete, RS, Brasil - SCHERER, CAROLINA SALDANHA; DA ROSA, ÁTILA AUGUSTO STOCK (Pesquisas em Geociências, 2003)
<!– .p text-align: justify; –> Fossil mammals and reptiles were found at the basal conglomeratic level from the Salatiel II outcrop, Sanga da Cruz, Alegrete, Rio Grande do Sul, which gave an approximate thermoluminescence age of 14.000 years BP (before present). The fossil herein studied consists of a left dentary fragment of a horse, identified from the occlusal teeth surface as Hippidion cf. Hippidion principale. A preliminary analysis of the associated fauna permits to achieve some paleoclimate inferences for the region, presumably colder than the present.